2012
DOI: 10.1007/s11126-012-9237-z
|View full text |Cite
|
Sign up to set email alerts
|

Delusional Misidentification Syndromes in Obsessive–Compulsive Disorder

Abstract: Delusional misidentification syndromes (DMS) have been rarely reported in patients with conditions other than schizophrenia-related disorders, diffuse brain disease (dementia) and focal neurological illness. In this report, we describe DMS (i.e. Capgras and Fregoli syndromes) in two patients with severe and treatment resistant obsessive-compulsive disorder (OCD), one with paranoid personality disorder (PPD) and the other with a pervasive developmental disorder (PDD) not otherwise specified. While our findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Moreover, in a case of obsessive-compulsive disorder, a nondelusional variant of Capgras syndrome characterized by doubts regarding the substitution by doubles has been reported in literature 28. Another study of cases of delusional misidentification syndromes in subjects suffering from obsessive-compulsive disorder suggested that these syndromes could be the result of an association between obsessive fears and pre-existing cognitive deficits 29. We know from the literature that Capgras syndrome is associated with organic illness in up to 40% of cases 5.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a case of obsessive-compulsive disorder, a nondelusional variant of Capgras syndrome characterized by doubts regarding the substitution by doubles has been reported in literature 28. Another study of cases of delusional misidentification syndromes in subjects suffering from obsessive-compulsive disorder suggested that these syndromes could be the result of an association between obsessive fears and pre-existing cognitive deficits 29. We know from the literature that Capgras syndrome is associated with organic illness in up to 40% of cases 5.…”
Section: Discussionmentioning
confidence: 99%
“…Fregoli delusion has also been associated with bipolar schizoaffective disorder and Hashimoto thyroiditis (Ceylan et al, 2010). Melca et. al.…”
Section: Fregoli Delusionmentioning
confidence: 99%
“…Many DMS are often associated with psychoses and have only rarely been reported in non-psychotic individuals. They are, nevertheless, fairly uncommon, occurring in about 4% of patients presenting with functional psychoses (Melca et al, 2013).…”
Section: Introductionmentioning
confidence: 99%